Fintech founders inspiring tales from the entrepreneurs that are changing finance - Rubini, Agustín (De Gruyter, 2020)
"Over 70 in-depth interviews of Fintech Founders provide lessons from some of the most successful fintech entrepreneurs that will help you understand the challenges and opportunities of applying technology and collaboration to solve some key problems of the financial services industry. This book is for entrepreneurs, for people working inside of large organizations and everyone in between who is interested to learn the secrets of successful entrepreneurs. In this advice-filled resource, Rubini gathers advice that comes from a diverse range of financial services niches including financing, banking, payments, wealth management, insurance, and cryptocurrencies, to help you harness the insights of thought leaders. Those working inside the financial services industry and those interested in working in or starting up businesses in financial services will learn valuable lessons on how to take an idea forward, how to find the right business founders, how to seek funding, how to learn from initial mistakes, and how to define and reposition your business model. Rubini also inquires into the future of fintech and uncovers provoking and insightful predictions."--